Special issue on climate-smart agriculture (CSA) - Campbell, Bruce M.; Dinesh, Dhanush (2017)
CSA strategies, policies, partnerships and investments; ‘CSA-Plan’: strategies to put CSA into practice; The mitigation pillar of CSA; Agricultural diversification as an adaptation strategy; Climate services and insurance: scaling; CSA Closing the gender gap in agriculture under climate change; How can the Data Revolution contribute to climate action?; Climate change and CSA in the current political climate